The Influence of Work Life Balance, Job Embeddedness, and Organizational Culture on Performance with Work Productivity as An Intervening Variable of Employees at Andi Publisher in Yogyakarta - Daeli, Iman Putra; Yokanan, Raden Teja; Kaloeti, Ade Kristianus (SEIKO : Journal of Management & Business, 2024)
The objective of this research is to examine the impact of work-life balance, job embeddedness, and organizational culture on performance through the lens of work productivity. The study employs a quantitative research methodology, utilizing a sample of 110 employees from the Publishing, Marketing, Production, Human Resources, and Finance Departments at Andi Publisher in Yogyakarta. Data collection was conducted through a questionnaire distributed directly to respondents, employing a simple random sampling technique. Data analysis was performed using SmartPLS version 4.0. The findings indicate that work-life balance has a positive effect on performance, while job embeddedness and organizational culture do not significantly influence performance. Additionally, work-life balance positively affects work productivity, and job embeddedness also has a positive impact on work productivity, whereas organizational culture does not. Furthermore, work productivity is positively correlated with performance. Notably, work productivity serves as a mediator for the relationship between work-life balance and performance, as well as between job embeddedness and performance, while it does not mediate the relationship between organizational culture and performance.